Effect of pore size and electrolyte flow rate on the bubble removal efficiency of 3D pure Ni foam electrodes during alkaline water electrolysis. Issue 3 (June 2022) - Rocha, Fernando; Delmelle, Renaud; Georgiadis, Christos; Proost, Joris
Abstract: To further reduce the capital expenditure of alkaline water electrolyzers, an improvement in power density can still be achieved through process intensification. The change from traditional gap-cells to zero-gap cells has already been proven to be very promising in this respect. In the zero-gap design, macro-porous 3D structures are typically being used as electrodes. Here, pure nickel foams with different pore sizes in the range 450 – 3000 µm have been studied under well-controlled electrolyte flow conditions. To this end, a dedicated flow cell has first been constructed that allows for imposing the same relatively high flow rates on the order of 1 L/min that are typically encountered under industrial conditions. Our specific cell design was shown by computational fluid dynamic simulations to be able to homogenize the flow field before entering the electrodes. This is absolutely mandatory to reliably evaluate the intrinsic bubble removal efficiency of the differently sized foams. We then demonstrate that the effect of pore size and the electrochemical performance can be rationalized by considering the cell voltage as a function of electrochemical current density, i.e. the current divided by the theoretically available electrochemical surface area (ECSA) rather than by the projected electrode area. Based on this analysis, we were also able to quantify the bubble removal efficiency by estimating the effective fraction of the ECSA that is not impeded by bubble coverage. Graphical Abstract: ga1 Highlights: Ni foams with pore sizes from 450 to 3000 µm have been studied under well-controlled electrolyte flow conditions. Our cell design was shown by CFD simulations to be able to homogenize the flow field. The effect of pore size can be rationalized by considering the cell voltage as a function of electrochemical current density the ECSA. The bubble removal efficiency was quantified by the effective fraction of the ECSA that was not impeded by bubble coverage.